Physical Function and Quality of Life After Resection of Mobile Spine Chondrosarcoma. Issue 7 (October 2019) - Paulino Pereira, Nuno Rui; Janssen, Stein J.; Stoop, Nicky; Hartveldt, Stefan; Chen, Yen-Lin E.; DeLaney, Thomas F.; Hornicek, Francis J.; Schwab, Joseph H.
Study Design: Retrospective cohort study. Objectives: (1) To assess patient-reported outcomes—physical function, pain, and quality of life—in patients who underwent resection of a mobile spine chondrosarcoma. (2) To assess complications (90 days), readmissions, reoperations, oncological outcomes, and neurologic status. Methods: Thirty-three patients with spinal conventional chondrosarcoma resection between 1984 and 2014 at one hospital were included. The primary outcome measures were—minimally 6 months after surgery—the EuroQol 5 Dimensions (EQ5D), PROMIS–Physical Function, PROMIS–Pain Intensity, and Oswestry (ODI) Disability Index, or Neck (NDI) Disability established in 14 out of 20 alive (70.0%) patients. Complications, readmission, reoperations, oncological outcomes, and neurological status were reported for the complete cohort of 33 patients. Results: After spine chondrosarcoma resection, patients (n = 14) reported worse physical function (median 43, range 22-61, P = .026), worse quality of life (median EQ5D 0.70, range 0.04-1, P = .022), and comparable pain intensity (median 47, range 31-56, P = .362) when compared with US general population values. The median NDI/ODI was 25 (range 0-72) indicating mild to moderate disability. Patients undergoing reoperation had worse patient-reported outcomes than those who did not. Eighteen (55.5%) out of 33 patients suffered complications (90 days), 14 (42.4%) had unplanned readmission, and 13 (39.4%) underwent reoperation. Intralesional resection was associated with increased readmission, reoperation, and recurrence rate. Conclusions: Chondrosarcoma affects quality of life and physical function and its treatment frequently results in complications and reoperations. Our findings can be used to inform future patients about expected outcomes.